Respuesta :

Given:

The function is

[tex]f(x)=-\dfrac{1}{2}\sqrt{x+3},x\geq -3[/tex]

To find:

The inverse of the given function.

Solution:

We have,

[tex]f(x)=-\dfrac{1}{2}\sqrt{x+3}[/tex]

Put f(x)=y.

[tex]y=-\dfrac{1}{2}\sqrt{x+3}[/tex]

Interchange x and y.

[tex]x=-\dfrac{1}{2}\sqrt{y+3}[/tex]

Isolate the variable y.

[tex]-2x=\sqrt{y+3}[/tex]

[tex](-2x)^2=y+3[/tex]

[tex]4x^2-3=y[/tex]

[tex]y=4x^2-3[/tex]

Putting [tex]y=f^{-1}(x)[/tex], we get

[tex]f^{-1}(x)=4x^2-3[/tex]

For [tex]x\geq -3[/tex],

[tex]x+3\geq 0[/tex]

[tex]\sqrt{x+3}\geq 0[/tex]

[tex]-\dfrac{1}{2}\sqrt{x+3}\leq 0[/tex]

[tex]f(x)\leq 0[/tex]

It means for function [tex]f(x)\leq 0[/tex] and for inverse function [tex]x\leq 0[/tex] because the range of the function is the domain of inverse function.

Therefore, [tex]f^{-1}(x)=4x^2-3[/tex] for [tex]x\leq 0[/tex].